2022
DOI: 10.3389/fpsyg.2022.1017202
|View full text |Cite
|
Sign up to set email alerts
|

Is not workplace gossip bad? The effect of positive workplace gossip on employee innovative behavior

Abstract: PurposeThe purpose of this study is to examine the role of positive workplace gossip (PWG) in employee innovative behavior, whereby a mediating effect of employee loyalty is proposed in this relationship. The moderating effect of organizational trust (OT) is also examined on the indirect of PWG on employee innovative behavior through employee loyalty.Design/methodology/approachThis research used a survey data of 327 employees from the enterprises selected from the Pearl River and Yangtze River Delta region of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Regarding control variables, Prabhu et al (2023) showed that female subordinates found it unprofessional for male coworkers to relay team leaders’ instructions to them as they perceived them as uncivil. Subordinates in their 30s or less reported experiencing incivility significantly more often than their coworkers in their 40s (Dai et al , 2022). However, older coworkers tend to have rude conversations with supervisors about younger coworkers because they are trusted and fear the organization’s reputation from such supervisors’ views (Climek et al , 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Regarding control variables, Prabhu et al (2023) showed that female subordinates found it unprofessional for male coworkers to relay team leaders’ instructions to them as they perceived them as uncivil. Subordinates in their 30s or less reported experiencing incivility significantly more often than their coworkers in their 40s (Dai et al , 2022). However, older coworkers tend to have rude conversations with supervisors about younger coworkers because they are trusted and fear the organization’s reputation from such supervisors’ views (Climek et al , 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The “organizational” context is the first layer, which includes elements such as organizational trust (Dai et al , 2022). This link is bidirectional, meaning that workplace gossip may impact and influence the overall organizational setting.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Gossip is ubiquitous. In daily life, people often hear, participate in or spread other people's gossip intentionally or unintentionally, and use it as an important way to obtain information, vent emotions and maintain relationships (8). In the specific social situation of the workplace, positive and negative gossip can be distinguished in the workplace, with the latter's prevalence and worry rates being of more concern (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…According to the conservation of resources theory, individuals exhibit a proclivity to uphold, safeguard, and obtain resources (24), and the loss of resources will lead to negative behaviors of employees (19). Specifically, negative gossip in the workplace makes employees feel isolated, worsens the interpersonal relationship among employees (8,25), and increases the uncertainty and instability of work tasks (26), leading to serious depletion of employees' emotional and psychological resources (27). The depletion of emotional and psychological resources has a detrimental impact on employee enthusiasm and dedication, posing challenges for employees in fully engaging with their work.…”
Section: Introductionmentioning
confidence: 99%